Becoming a certified Vault operations professional : a complete guide. (Packt Publishing, 2023)
The primary objective of the course is to help you pass the HashiCorp Certified: Vault Operations Professional certification. It also prepares you to answer MCQs and perform hands-on tasks on a Vault node/cluster. This course teaches you how to create a working Vault server configuration for various scenarios. You will learn how to monitor a Vault environment to ensure its smooth functioning. It also covers how to employ the Vault security model to safeguard your system. You will then learn how to build fault-tolerant Vault environments that can withstand failures and disruptions. Following that, you will understand the integration of the Hardware Security Module (HSM) in Vault to increase security. You will see how to scale Vault for performance and handle a larger workload and how to configure access control to ensure that users have the right permissions to access data. After that, you will see how to configure the Vault agent for the automation of Vault operations. Finally, you will get an insight into the exam experience and expectations to prepare yourself better for the Vault Operations Pro certification exam. By the end of this course, you will be fully equipped with the skills and knowledge needed to pass the Vault Operations Professional exam and gain a solid foundation in Vault and be able to confidently use it in your organization. What You Will Learn Create a working Vault server configuration given a scenario Monitor a Vault environment and employ the Vault security model Build fault-tolerant Vault environments Understand the Hardware Security Module (HSM) integration Scale Vault for performance Configure access control and Vault Agent Audience This course is designed for DevOps engineers, cloud architects, security engineers, IT professionals, system administrators, network engineers, and infrastructure engineers. Advanced Vault operators who are looking to increase their knowledge and engineers will gain a lot from this course. To get the most out of this course, one should have earned their Vault Associate certification and have a solid understanding of Vault concepts, components, and deployment. The course assumes prior knowledge of Vault components such as storage backends, auth methods, secret engines, and Vault devices. Note that this is not an introductory-level course and will not cover Vault basics. About The Author Bryan Krausen: Bryan Krausen is an IT consultant with over 20 years of experience in enterprise IT. He specializes in Amazon Web Services and HashiCorp tools. Bryan focuses on cloud design and facilitates customer workshops that define business and technical requirements to allow businesses to deliver applications on the AWS cloud platform. He was the first individual to earn the HashiCorp Vault Expert partner certification. Bryan has deployed and assisted with adopting the HashiCorp Vault into many Fortune 1000 companies. He delivers lectures at community events, such as HashiConf (2019 to 2022), HashiTalks (2019 to 2020), and many HashiCorp user groups across the mid-west and eastern US.